FORMATION OF ANTIQUE RHETORIC: CHRONOLOGY OF RHETORICAL METHODS AND STYLES (PLATO, ARISTOTLE) - Pantelyeyeva, Irina A. (Anthropological Measurements of Philosophical Research, 2013)
Purpose of the article: to analyze the basic points of philosophical concepts of rhetoric of Plato and Aristotle, to prove that from Plato the rhetoric in the true sense starts being approved, and Aristotle is an ancestor of real theory of speech of the new genre, the new form, the new purposes and tasks of the description of verbal art. Problem statement: development of the ancient principles of rhetorical style’s creating is reached by efforts of outstanding speakers, each of them were differed not only by the ideological sympathies or antipathies, but also by nature of works, the concepts put in their basis. Two Ancient Greek philosophers: Plato and Aristotle are considered as founders of ancient rhetorical science. Methodology. Author has used system method, methods of content and comparative analysis. Scientific novelty is displayed in the received results from the comparative analysis of two concepts of public speech of Plato and Aristotle from a position of philosophical justification of rhetoric’s rules with orientation on ancient "popular" declamation practices. Practical value of article consists in development of insufficiently studied object "Antique declamation discourse" where Plato and Aristotle’s two central rhetorical concepts appear as the intermediate stage in development of a declamation discourse of Ancient Greece and, subsequently, and Ancient Rome. Conclusions. The conclusions can be given by the following facts: from Plato the rhetoric in the true sense is approved: true rhetorical art isn’t based only on argument technique, the true rhethor appears as the philosopher. Plato raises the problem of an ambiguity of two opposite rhetorics presented in "Gorgias" and "Phaedrus ". Rhetoric as scientific discipline, as the present theory of speech is first considered by Aristotle. The rhetoric is presented as the science "about speech and about thoughts", about the relation of thinking to the word.